A Multimodal Hair-Loss Treatment Strategy Using a New Topical Phytoactive Formulation: A Report of Five Cases - Sanusi Umar; Marissa J. Carter (Hindawi Limited, 2021)
Introduction. Current approved medications for hair loss, such as topical minoxidil and oral finasteride, may have suboptimal efficacy or side effects precluding continued use in some patients. Thus, we report an evaluation of the efficacy, safety, and tolerability of a new topical botanical formulation -GASHEE containing over 12 phytoactive ingredients that affect multiple targets in the cascade of pathophysiologic events that cause hair loss. Five patients with various hair-loss conditions, including cases of previous treatment failures, are presented. Case Presentation. This is a case series of four women and one man with hair loss due to various causes, four of whom had failed minoxidil treatment for over a year. All patients used the topical treatment as a sole therapy for at least 3 months before the documentation of outcomes, which involved interval changes noted through each patient's account, direct observation, and photography. Discussion. In all patients, we observed significant improvements in hair regrowth in the nape, crown, vertex, and temple areas after 3-15 months of treatment. All patients were highly satisfied with their results and reported no adverse events. Although the use of botanicals in the treatment of hair loss is in an infant stage, the new formulation used in this study demonstrated a good efficacy related to hair growth, warranting further evaluation.